La production du « vrai musulman » par l’organisation des Frères musulmans égyptiens : fidélité et dissidences - Sarah Ben Néfissa (Revue Internationale des Études du Développement, 2017)
Mentoring youth is one of the core activities of the Egyptian Muslim Brotherhood. They believe that political reform is the result of individuals’ religious reform. The article analyzes the form of the organization’s educational outreach. The analysis is based on the Brotherhood’s literature setting forth its pedagogical principles, as well as on internal documents organizing their implementation, and testimonies published by former young Muslim Brothers. Producing a “Real Muslim“ depends on the organization’s emotional dimension as much as on the monitoring and the control of the people. The article highlights the importance of the cultural factor, which is the main resource for disengagement.